Efektivitas Ekstrak Biji Andaliman (Zanthoxylum acanthopodium)dan Rimpang Jahe (Zingiber officinale) dalam Menghambat Pertumbuhan Staphylococcus sp. - Siregar, Siti Aisah; Fauziah, Ida; Sartini, Sartini; Rahmiati, Rahmiati (Universitas Medan Area, 2024)
Andaliman seeds contain compounds such as alkaloids, glycosides, carbohydrates, tannins, phenols, flavonoids, steroids, oils, and fats. Ginger rhizomes contain alkaloids, flavonoids, phenolics, triterpenoids, and saponins. This study aims to evaluate the antibacterial activity of Andaliman seed and ginger rhizome extracts against Staphylococcus sp. The method used is a Completely Randomized Design (CRD) with varying extract concentrations (25%, 50%, 75%, and 100%). Distilled water is used as a negative control and chloramphenicol as a positive control, with three repetitions for each treatment. The results show that Andaliman seed extract can inhibit the growth of Staphylococcus sp., with the largest inhibition zone at a 100% concentration (3.2 mm) and the smallest at 25% (1.3 mm). For ginger rhizome extract, the largest inhibition zone is also at a 100% concentration (2.5 mm) and the smallest at 25% (1.1 mm). ANOVA and LSD tests indicate significant differences in the inhibition zone diameters across extract concentrations, with the 75% concentration showing the best results.